Long term clinical outcome of a randomised controlled trial of anterior chamber lenses after high volume intracapsular cataract surgery. Issue 1 (1st January 2001) - Hennig, A; Johnson, G J; Evans, J R; Lagnado, R; Poulson, A; Pradhan, D; Foster, A; Wormald, R P L
Abstract : BACKGROUND: Age related cataract remains the major cause of blindness throughout the world. In many countries, the majority of cataract surgery continues to be done by the intracapsular cataract extraction (ICCE) method. The results of a large randomised controlled trial of multiflex open loop anterior chamber intraocular lenses (ACIOL) were reported from a busy eye hospital in Nepal. METHODS: There was a randomised controlled trial of 2000 people with bilateral cataract reducing vision to less than 6/36. Interventions were ICCE with an ACIOL compared with ICCE with aphakic spectacles (+11 dioptres). Participants were followed at discharge, 6 weeks, 1 year, and 1½–5 years after surgery. Visual acuity and clinical outcome were measured. A poor outcome was defined as vision <6/60. RESULTS: Visual outcome was comparable in the two groups. More of the control group experienced functional blindness due to loss of aphakic spectacles at 1 year. The majority of cases of poor outcome occurred in the first year after surgery. There was no indication of any lens related problems after 1 year. CONCLUSION: Multiflex open loop anterior chamber lenses are safe for up to 1 year of follow up when used by experienced surgeons, and the available evidence of 2–5 years of follow up suggests that the complication rate is reasonably low. An ACIOL at the time of cataract surgery offers benefits over routine ICCE surgery with aphakic spectacle correction as it avoids the problem of replacing lost and broken spectacles.